CNC PART PROGRAMMING TECNIQUE AND CREATING CYLINDIRICAL PLOUGH ACTIVE SURFACE BY USING THIS TECHNIQUE - Yaşar KARAGÖZ; Galip KEÇECİOĞLU (Pamukkale University Journal of Engineering Sciences, 2001)
"CNC" is an abbreviation for computer aided numerical control systems. Thanks to this system, operators can achieve a lot of work which cannot be realized by classical looms, in a short time, with higher quality in cheaperway. The term of "Part Programming" defines a group of commands to be included in the loom control unit of a loom which is designed to process a part or a certain machine element having have some certain technological methods and functions. In this work, CNC part programming and processing methods are applied to the manufacturing of active surface of a cylindirical plough on CNC loom was investigeted.